Extent of Anaemia among Preschool Children in EAG States, India: A Challenge to Policy Makers - Rakesh Kumar Singh; Shraboni Patra (Anemia)
Background. India is the highest contributor to child anemia. About 89 million children in India are anemic. The study determines the factors that contributed to child anemia and examines the role of the existing programs in reducing the prevalence of child anemia particularly in the EAG states. Methods. The data from the latest round of the National Family Health Survey (NFHS-3) is used. Simple bivariate and multinomial logistics regression analyses are used. Results. About 70% children are anemic in all the EAG states. The prevalence of severe anemia is the highest (6.7%) in Rajasthan followed by Uttar Pradesh (3.6%) and Madhya Pradesh (3.4%). Children aged 12 to 17 months are significantly seven times (RR=7.99, P<0.001) more likely to be severely anemic compared to children of 36 to 59 months. Children of severely anemic mothers are also found to be more severely anemic (RR=15.97, P<0.001) than the children of not anemic mothers. Conclusions. The study reveals that the existing government program fails to control anemia among preschool children in the backward states of India. Therefore, there is an urgent need for monitoring of program in regular interval, particularly for EAG states to reduce the prevalence of anemia among preschool children.